ANALISIS PLTS ATAP ON GRID 618,8 KWP PADA GEDUNG UNIVERSITAS HKBP NOMENSEN - Helmi Putra, Satria; Muhaammad Fitra Zambak; Suwarno; Rohana (LPPM STMIK Lombok, 2024)
Indonesia is currently highly dependent on fossil fuels whose availability is limited and has an emission effect on the environment, for the sustainability of the availability of electrical energy, alternative energy sources are needed in the form of new renewable energy, one of which is the Solar Power Plant (PLTS). This study discusses the analysis of rooftop PLTS on the 618.8 Kwp network at HKBP Nommensen University Medan using data from the Fusion Solar application. To analyze the effect of PLTS injection into the electricity network. The process of collecting UHN PLTS electricity data and measuring progress on changes that focus on the PLTS process and output was carried out from August 1 to August 31, 2023. The data collection in question is solar energy data that emits light and heat (irradiance) which can be utilized as an energy source through Photo Voltaic which produces certain electrical power. Furthermore, the activity to check or investigate the condition of the PLTS through the data above is to find out the actual condition of the PLTS. Data can be observed from and until the date above, and produces a total energy for consumption of 34.81 MWH and for export of 25.75 MWH with a total PLTS production of 60.56 MWH. And import data that occurred during August 2023 with a total of 0.3 KWH. With the injection of PLTS power into the grid, it can increase the large voltage on the bus that is directly connected to the PV.